(untitled) - FAO (Rome, Italy, 2005)
This CD-ROM is aimed at enhancing information access and exchange to improve the safe production, harvesting, handling, storage, transport and marketing of fresh fruits and vegetables. The database resource materials and training activities are structured so that users will understand the relationship between quality and safety issues. The CD-ROM has four modules are: Hazards and quality issues; Safety and quality programs and systems; Food laws, regulations, standards and grades; The Services
Keywords: Fruits,Vegetables